Analisis Pengukuran Kualitas Aplikasi Pendataan Warga Menggunakan Metode Six Sigma pada Perumahan Griya Sejahtera Palembang - Monika Sima; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid advancement of digital technology has encouraged various sectors, including government and housing management, to adopt application-based systems for data collection and administration. The Citizen Data Collection Application at Griya Sejahtera Housing, Palembang, aims to facilitate population data management. However, its quality and performance need to be measured systematically to ensure it meets user expectations. This study applies the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) framework to measure and analyze the quality of this application. The research employs a quantitative approach by collecting user complaint data, defect identification, and questionnaire analysis. The results reveal that the application's sigma level is at 2.18, indicating relatively low quality with a DPMO (Defects Per Million Opportunities) value of 279,069. The highest defect types found include data entry errors, slow application response, and unsynchronized synchronization. Proposed improvements include enhanced feature testing, user interface simplification, and periodic evaluation. This study contributes to efforts to improve the quality of application-based public services and offers practical recommendations for housing managers and application developers.